Loanwords in Basic Vocabulary as an Indicator of Borrowing Profiles - De Heer, Mervi (Brill Academic Publishers, 2025)
Loanwords carry information on linguistic interactions, and can also reveal (pre-)historical population contacts. The contact history of a particular language family is an essential component of historical linguistics, but it is also illuminating for integrative studies of the human past. However, data availability and the time-consuming nature of etymology mean that comprehensive research on loanword layers exists for relatively few languages, forcing us to rely on limited material for others. This paper compares the loanword layers in the basic and total vocabulary of six well-studied Uralic languages, assessing how accurately the borrowing profile in basic vocabulary reflects the full profile of a language. We define "borrowing profile"as the known contact history of a language reflected by its loanword layers. We demonstrate that the loanword layers in basic vocabulary provide an adequate cross-section of the full borrowing profile, although basic vocabulary manifests prehistoric contacts more strongly than more recent contacts.